Analysis of the Effect of Memberly Card and Customer Experience on Customer Loyalty in Mediation by Customer Satisfaction (Case Study on Tasik Pharmacy in Sukabumi City) - Alif Rengga Gunawan; Ade Sudarma; Leonita Siwiyanti (International Journal of Economics, Management and Accounting (IJEMA), 2025)
In the pharmaceutical industry, customer loyalty is a crucial factor for the sustainability of the pharmacy business. One strategy used to increase customer loyalty is to implement a Memberly Card membership program and provide a quality shopping experience (Customer Experience). However, there are still limitations in understanding how these two factors affect Customer Loyalty, especially considering the role of Customer Satisfaction as a mediating variable. This study aims to analyze the effect of Memberly Card and Customer Experience on Customer Loyalty, with Customer Satisfaction as a mediating variable. This study was conducted on customers of Apotek Tasik in Sukabumi City using a quantitative approach with a cross-sectional research design. The purposive sampling method was used to determine a sample consisting of 126 respondents, according to the Hair formula (2018). Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results of the study indicate that Memberly Card has a positive and significant effect on Customer Satisfaction (β = 0.506; p = 0.012) and Customer Loyalty (β = 0.457; p = 0.016). Likewise, Customer Experience has a positive effect on Customer Satisfaction (β = 0.293; p = 0.036) and Customer Loyalty (β = 0.268; p = 0.033). In addition, Customer Satisfaction is proven to have a positive and significant effect on Customer Loyalty (β = 0.215; p = 0.027). These findings indicate that membership-based loyalty programs and positive customer experiences can increase customer satisfaction and loyalty to pharmacies. This study provides practical implications for pharmacy managers to improve loyalty programs and improve customer experience to strengthen customer loyalty. This study also enriches the literature on factors that influence Customer Loyalty in the pharmaceutical industry.